Proceedings of the 25th International Conference Companion on World Wide Web - WWW '16 Companion 2016
DOI: 10.1145/2872518.2890085
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and the Relationship with (Non-) Disclosure Behavior on Facebook

Abstract: Applications increasingly use personality traits to provide a personalized service to the user. To acquire personality, social media trails showed to be a reliable source. However, until now, analysis of social media trails have been focusing on what has been disclosed: content of disclosed items. These methods fail to acquire personality when there is a lack of content (non-disclosure). In this study we do not look at the disclosed content, but whether disclosure occurred or not. We extracted 40 items of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In the last couple of years, it has been demonstrated that personality information can be extracted from social networking sites (SNSs) like Facebook (e.g., [2,35,42,73,81]), Twitter (e.g., [41,75]), and Instagram (e.g., [29-31, 36, 65], or a combination of such [89]). Being able to extract personality traits from SNSs caters the possibility for (music) applications to adjust their user interface based on our results.…”
Section: Discussionmentioning
confidence: 99%
“…In the last couple of years, it has been demonstrated that personality information can be extracted from social networking sites (SNSs) like Facebook (e.g., [2,35,42,73,81]), Twitter (e.g., [41,75]), and Instagram (e.g., [29-31, 36, 65], or a combination of such [89]). Being able to extract personality traits from SNSs caters the possibility for (music) applications to adjust their user interface based on our results.…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in self-representation should be considered a continuous variable. Previous studies have demonstrated that profile pictures can be quantified using fine-grained analyses to detect different features of online self-representation, which provide a powerful measurement to predict personality traits [ 17 , 33 ]. Therefore, future studies investigating the relations between profile pictures using these in-depth analyses, personality, and life satisfaction would provide insights into the roles of online self-representation in the subjective well-being of internet users.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically related to the music domain, an increasing amount of work has been done on identifying related behaviors to these traits (e.g., [8,14,31]) as well as work that has proposed to incorporate these traits into personalization and adaptation solutions (e.g., [3,5,7,23]). Furthermore, attention has been given to implicitly acquire personality traits for personalization purposes by the use of (external) information sources, such as Facebook (e.g., [1,10]), Twitter (e.g., [26]), Instagram (e.g., [9,[11][12][13]22]), or a combination of such [30].…”
Section: Related Workmentioning
confidence: 99%